Association between breakfast consumption and educational outcomes in 9–11-year-old children. Issue 9 (28th September 2015) - Littlecott, Hannah J; Moore, Graham F; Moore, Laurence; Lyons, Ronan A; Murphy, Simon
Abstract: Objective: Breakfast consumption has been consistently associated with health outcomes and cognitive functioning in schoolchildren. Evidence of direct links with educational outcomes remains equivocal. We aimed to examine the link between breakfast consumption in 9–11-year-old children and educational outcomes obtained 6–18 months later. Design: Data on individual-level free school meal entitlement and educational outcomes (Statutory Assessment Tests (SATs) at Key Stage 2) were obtained via the SAIL databank and linked to earlier data collected on breakfast consumption. Multilevel modelling assessed associations between breakfast consumption and SATs. Setting: Trial of the Primary School Free Breakfast Initiative in Wales. Subjects: Year 5 and 6 students, n 3093 (baseline) and n 3055 (follow-up). Results: Significant associations were found between all dietary behaviours and better performance in SATs, adjusted for gender and individual- and school-level free school meal entitlement (OR=1·95; CI 1·58, 2·40 for breakfast, OR=1·08; CI 1·04, 1·13 for healthy breakfast items). No association was observed between number of unhealthy breakfast items consumed and educational performance. Association of breakfast consumption with educational performance was stronger where the measure of breakfast consumption was more proximal to SATs tests (OR=2·02 measured 6 months prior to SATs, OR=1·61 measured 18 months prior). Conclusions: Significant positive associations between self-reported breakfast consumption and educational outcomes were observed. Future research should aim to explore the mechanisms by which breakfast consumption and educational outcomes are linked, and understand how to promote breakfast consumption among schoolchildren. Communicating findings of educational benefits to schools may help to enhance buy-in to efforts to improve health behaviours of pupils.